Anti-Proliferative Activity of Nigella sativa Chloroform Extract on 7,12-Dimenthylbenz[a]anthracene Induced Female Rats Splenocyte - Firdaus, Ahmad Fiki; Sobri, Iskandar; Ekowati, Heny (Indonesian Research Gateway, 2012)
Previous study reported that Nigella sativa has in vitro and in vivo cancer activity. This study was conducted to observe the effect of chloroform extract of Nigell sativa seed (NCE) on 7,12-Dimethylbenz[a]anthracene (DMBA)-induced female rats splenocyte. The experiment consisted of five groups, corn oil solvent control group, DMBA group, DMBA+250 mg/kgBW NCE, DMBA+500 mg/kgBW NCE and DMBA+750 mg/kgBW NCE. Extract was dissolved in corn oil and oral administered daily for 2 weeks before and during the DMBA induction. Observation of cell proliferation was performed using haematoxylin and eosin (H&E) and AgNOR stainings. H&E staining showed decreased necrocis activity extract groups compared to DMBA group. From AgNOR staining results, mean AgNOR (mAgNOR) of extract groups was less in number compared to DMBA group. The mAgNOR in corn oil solvent control group, DMBA group, DMBA+250 mg/kgBW NCE, DMBA+500 mg/kgBW NCE and DMBA+750 mg/kgBW NCE were 1.22, 1.91, 1.29, 1.36 and 1.33, respectively. Our current results showed that NCE reduces the proliferation of DMBA-induced rat spleenocytes. Thus, NCE has potency to be developed as a chemopreventive agent.Keywords : Nigella sativa, spleen, DMBA, anti-proliferative